2022
DOI: 10.3389/fragi.2022.820215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials Targeting Aging

Abstract: The risk of morbidity and mortality increases exponentially with age. Chronic inflammation, accumulation of DNA damage, dysfunctional mitochondria, and increased senescent cell load are factors contributing to this. Mechanistic investigations have revealed specific pathways and processes which, proposedly, cause age-related phenotypes such as frailty, reduced physical resilience, and multi-morbidity. Among promising treatments alleviating the consequences of aging are caloric restriction and pharmacologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Excessive BA (or biological age acceleration) is associated with all-cause mortality, the prevalence, future incidence, and severity of chronic [9,16,17] and transient diseases, including COVID-19 [15,[18][19][20]. Hence, BA predictors have increasingly gained traction in clinical trials [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive BA (or biological age acceleration) is associated with all-cause mortality, the prevalence, future incidence, and severity of chronic [9,16,17] and transient diseases, including COVID-19 [15,[18][19][20]. Hence, BA predictors have increasingly gained traction in clinical trials [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin, as well as its analogue, Sirolimus, was approved by the FDA in 1999 for use as an immunosuppressant. Accordingly, its role in the treatment of cancer has been widely reviewed [ 102 , 103 ], and multiple clinical trials evaluating its efficacy for the treatment of multiple cancers and the development of neurological diseases are ongoing.…”
Section: Clinical Trials Aimed At Delaying the Ageing Processmentioning
confidence: 99%
“…Interestingly, recent cross-species study reported on uterine lavage using human PRP to treat mouse intracavitary uterine synechiae (Kim et al, 2022), where significantly increased STAT3 phosphorylation (a critical transcription factor in tissue regeneration) was observed with upregulated Mt2-mmp, Lox, and Adm, all mediators of tissue remodeling. Cell proliferation, maintenance of genome stability, and metabolic regulation are all influenced by sirtuins (Nielsen et al, 2022), which are nicotinamide adenine dinucleotide (NAD)-dependent deacetylases. Investigators at Huazhong Science & Technology University discovered that SIRT1, SIRT3 and SIRT6 are closely related to ovarian reserve, and may serve as proxy markers of ovarian aging (Zhang et al, 2016).…”
Section: Measuring Menopause and How To Reset Itmentioning
confidence: 99%